Penguatan Program Inovboyo Untuk Mendukung Smart Society Dalam Pembangunan Smart City Kota Surabaya - Nur Faizatur Rohma; Amal Taufik; Masitah Effendi (Program Studi Ilmu Administrasi Negara Bekerjasama dengan Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2024)
This scientiﬁc paper discusses the strengthening of the Inovboyo program (innovation in the city of Suroboyo) to support smart society development in Surabaya as a smart city. The two main research questions addressed are how the Inovboyo program acts as a catalyst for innovation and stakeholder collaboration in Surabaya. The research method used is qualitative with a case study approach. The results indicate that the Inovboyo program has successfully promoted innovation and smart society development in Surabaya. Eﬀective stakeholder collaboration and the utilization of technology for publicity are key factors in the program's success